Preparation and application of different size materials on the cotton yarn and investigating the effect of sizing on the tensile properties of cotton yarn (Bangladesh Journal of Scientific and Industrial Research, 2014)
Sizing of the cotton yarn is essential to reduce breakage of the yarn due to abrasion during weaving process. The sizing agent on the woven fabric after weaving needs to remove completely before the next textile production process of dyeing and finishing. So, water soluble sizing agent is easy to handle and easy to desizing for pre-treatment of woven fabric. In this work, different types of water soluble tamarind seed kernel based sizing formulations (assigned by A, B and C) were made and applied on cotton yarn to investigate the effect on the tensile properties of sized and unsized cotton yarns. Cotton yarn treated with size B formulation shows the better tensile properties than the application of size A and size C formulation. The effect of lubricant has also been investigated and shows that the addition of lubricant decreases the tensile properties of the cotton yarn. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18850 Bangladesh J. Sci. Ind. Res. 49(1), 25-30, 2014